Profil Peresepan Obat Anti Hipertensi Pada Pasien Rujuk Balik Di Apotek X Periode Januari – Maret 2020 - Ahmad Suriyadi Muslim (Jurnal Indonesia Sehat, 2022)
Hypertension is a clinical condition of when someone has high blood pressure above normal which can increasing the risk for morbidity and mortality. Antihypertensive drugs group which are ACE inhibitors, ARBs, CCBs, either alone or a combination was used for the therapy. Combination antihypertensive drug is needed if a single antihypertensive drug has not been able to control the desired of the patient's blood pressure. A non-experimental descriptive method was used for this study. The research was carried out without giving anything to the studied variable. A retrospective approach with past data were the sample for this study and 574 prescription sheets were obtained. Variables in this study were include patient characteristics data and drug characteristics data. The results of the research was most of the patients were female with a total of 314 prescriptions (55%). The type of drug therapy which often used were combination therapy with 504 prescriptions (88%). The type of drug group which most usually used on the prescrition was CCB with 482 prescriptions (49%) and the name of the drug that was often prescribed was amlodipine which the amount were 479 prescriptions (49%).